Implementation of credit risk management basel principles (Evaluation Study of an Indonesian Commercial Bank) - Sutono, Joko; Hermawan, Ancella Anitawati (Politeknik Ganesha Medan, 2024)
The study evaluated the implementation of credit risk management at Bank PQR based on the Basel Principles regarding Management of Credit Risk due to increasing Low-Quality Credit in the last six months. It adopted a case study approach at Bank PQR, one of Indonesia's commercial banks, in the Corporate Segment with total credit reaching 62% of the Bank PQR credit portfolio using a qualitative descriptive method by conducting document analysis and interviews to collect data. The study sample consists of 30 credit-granting proposals of Bank PQR. First, it evaluated the suitability of the Basel Principles with the regulation of the Financial Services Authority, then analyze Bank PQR document, conduct an interview and last evaluated implementation of credit risk management by providing a score of three if suitable and implemented well, two if suitable and not implemented well and one if not suitable. The result shows the implementation is not by the Basel Principles with a final score of 2.58 out of 3, and the main weakness being the inadequacy of the credit risk environment’s development. It recommends the Bank PQR to improve its credit risk environment, such as compliance with regulations, employee training, and implementing good internal controls.